Disruptions in global supply chains and regional output in Mexico during the COVID-19 pandemic - Eva González; Cindy Rangel; Leonardo Torre; Alejandrina Salcedo; Jorge Alvarado (Banco de México, 2024)
The paper analyzes how the initial disruption in the supply of imported inputs associated to the COVID-19 pandemic may have induced heterogeneous responses in regional and sectoral gross output in México. Using the Regional Input-Output Matrices estimated by Banco de México, and the Supply Ghosh Model, the effects associated to the supply-side shock that ensued from the sudden reduction of imported inputs from China, the European Union, and the United States at the onset of the pandemic are calculated. The Northern region experienced the greatest contraction in gross output, while at the sectoral level, the manufacturing sector gross output was the most affected by the shock relative to a scenario with constant availability of inputs. These results are consistent with the fact that both, the Northern region and the manufacturing sector, are the most integrated to the global supply chain.
Keywords: R11; R12; R15; 330; COVID-19; Input-Output; Ghosh Model; Mexico